ETHNOGRAPHY OF CULTURAL COMMUNICATION WAYANG GOLEK MADE FROM WASTE IN BOGOR CITY, WEST JAVA - Ardianti, Dhini; Fariz, Muhammad (SAMPURASUN, 2024)
This research discusses the cultural communication of wayang golek performances made fromwaste in Bogor City, West Java. In the midst of the phenomenon of cultural degradation in bigcities, Sanggar Edas Bogor City is still maintaining the existence of wayang golek, especiallymaintaining cultural preservation while caring for the environment. This research uses anethnographic communication approach which consists of three stages, communicative situations,communicative events, and communicative actions. This research, which was conducted from 2023to 2024, used descriptive qualitative research methods through observation data collection,interviews and documentation studies. The research results show that the three stages of theethnographic communication study model, namely the communicative situation, explain that theconditions when communication occurs in a wayang golek performance are adjusted depending onthe place, time or communication activities in a wayang golek performance. The second stage,namely communicative events, explains that communicative events include all of the componentsand complete devices, starting from the purpose of communication, common topics throughmessages related to awareness of environmental damage due to uncontrolled waste, involvingparticipants who use the same language varieties, maintaining Sundanese language rules. the sameway to interact in a wayang golek performance. And the third stage, namely communicative action,is the process of exchanging environmental messages, ideas and feelings between the puppeteerand the audience